Different Factors That Influence the Rise of India and Indonesia - Chengxin Zhang (Insignia: Journal of International Relations, 2021)
India and Indonesia are among the largest economies in the world, and this was not something serious for China to pay attention to in the past. However, in this decade, these two countries have shown aggressive economic growth, compared to other developed and developing countries such as Russia and Mexico. India under the Modi administration launched the Digital India 2025 ambition in 2018 and a GDP target of 5 trillion USD, Indonesia under the Jokowi administration featured the Global Marine Fulcrum (GMF) and the target of becoming the 4th largest economy in the world by 2045. Both focus on many sectors, especially economic support infrastructures such as railroads, ports, and fast trains. In terms of military, India is already strong in the 4th position in the world, and Indonesia is still far below India, the 16th in the world. The current world situation is unstable, leading India to steps to strengthen ties with Western countries to stem China's growth. On the Indonesian side, it tends not to field close relations with the West and is still cooperating, both with the West and China to develop the country's potential and infrastructure. However, both of them still have the duty to become the foremost countries; India with the problem of unification, and adjusting its foreign policies to neighboring countries, and Indonesia need to finalize on innovation and domestic development.